2021
DOI: 10.3390/polym13071009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Experimental Two-Step Self-Etch Adhesive’s Bonding Performance and Resin-Dentin Interfacial Properties

Abstract: This study evaluated an experimental two-step self-etch adhesive (BZF-29, BZF) by comparing it with a reference two-step self-etch adhesive (Clearfil Megabond 2, MB) and a universal adhesive (G-Premio Bond, GP) for microtensile bond strength (μTBS) and resin-dentin interfacial characteristics. Twenty-four human third molars were used for the μTBS test. Bonded peripheral dentin slices were separated to observe the resin-dentin interface and measure the adhesive layer thickness with SEM. μTBS data of the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Chowdhury AFMA et al, following an SEM comparison of self-etch and multi-etch adhesives, obtained similar results to ours. The fewer steps that the adhesives protocol had, the more ineffective they became [43]. Additionally, the study by Kasahara Y et al concluded that three-step adhesives are superior to universal and two-step adhesives [44].…”
Section: Discussionmentioning
confidence: 99%
“…Chowdhury AFMA et al, following an SEM comparison of self-etch and multi-etch adhesives, obtained similar results to ours. The fewer steps that the adhesives protocol had, the more ineffective they became [43]. Additionally, the study by Kasahara Y et al concluded that three-step adhesives are superior to universal and two-step adhesives [44].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might occur due to further polymerization after 24 h. Notably, AP was bonded with the dentin bonding agent SE. Recent studies reported that when AP is bonded with SE, it has high and stable bonding performance with dentin substrates [ 24 , 25 ]. The bonding agent and primer SE includes the functional monomer 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP).…”
Section: Discussionmentioning
confidence: 99%